A Contemporary Approach to Holistic Brand Communication - Hannah Leimert; Philipp Scharfenberger; Torsten Tomczak (Marketing Review St.Gallen, 2021)
Brand–consumer interactions have changed radically over the past two decades. In this article, we outline a holistic approach to brand communication, taking into account the current communication landscape. We discuss the present importance of brand identities and specify four core fields of modern brand communication and their joint relevance for brand–consumer relationships. Finally, we identify specific management qualities relevant to navigating brands through an all-new world of brand communication.
Keywords: 650